Revelation and Reason : Prolegomena to Systematic Theology. - Gunton, Colin E. (Continuum International Pub. Group, 2008)
Colin Gunton was a world renowned scholar, systematic theologian and Reformed Church minister. Revelation and Reason is an in-depth analysis, derived from the annual lecture/seminar course he gave to MA students at King's College London. Approximately one-third of the work is a direct transcript, and analysis of the three two-hour lectures Colin Gunton gave at a break-neck speed: 1. 'From Reason and Revelation to Revelation And Reason'; 2. 'The Modern Problem in an Historical Context'; 3. 'Aspects of Karl Barth on Faith And Reason'. These lectures were a history, analysis and critique of Revel.